2019
DOI: 10.1021/acsapm.9b00722
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Energy Settled Crystallization Behaviors of Poly(l-lactic acid)

Abstract: Polymer crystallization is crucial to the properties of polymers, which are determined by thermal dynamics and kinetics. The formation of polymorphism has turned out to be very important for applications of poly(L-lactic acid) (PLLA), because it has evolved into a competitive commodity material over the past decade. In the in situ wide-angle X-ray scattering study, it shows the growth of α-crystal of thermally treated PLLA at T c = 80 and 90 °C, which was considered only appropriate for the crystallization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Infrared spectroscopy is usually employed to elucidate the covalent bonds or other interatom interactions such as hydrogen bonds within polymers. 24,60 The dynamics of helix structures 19,61,62 or stereocomplex 27,63,64 can be unearthed during melting and recrystallization with time resolved FTIR. It is observed that the helix shorter than crystalline stem length remain in melt state above T m both in polar and non-polar 19 polymers.…”
Section: Advances In Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared spectroscopy is usually employed to elucidate the covalent bonds or other interatom interactions such as hydrogen bonds within polymers. 24,60 The dynamics of helix structures 19,61,62 or stereocomplex 27,63,64 can be unearthed during melting and recrystallization with time resolved FTIR. It is observed that the helix shorter than crystalline stem length remain in melt state above T m both in polar and non-polar 19 polymers.…”
Section: Advances In Experimental Techniquesmentioning
confidence: 99%
“…The melt memory effect is essentially another phenomenon originated from the slow dynamics of polymer chains under external thermodynamic or mechanical effects and ubiquitous in almost all polymer materials. Meanwhile the characteristics of the polymer chains, such as degree of polymerization (DP), 57,[82][83][84] chain polarization, 24,62,81 steric hindrance, rigid segment, 18,61 branching, copolymerization, 13,21,32,85,86 and polydispersity index (PDI), 87 can affect the behavior of polymer melt memory effects. From the rich literature it is beyond doubt that the melt memory effect is controlled by a multivariable constitutive equation which is too complicated to solve analytically.…”
Section: Effects Of Chain Configurationsmentioning
confidence: 99%
“…Furthermore, this disordered phase has a melting point at a lower temperature than the α phase, so the α' crystals can be easily transformed into an α form by heating. [13] Hu et al [14] studied the cold crystallization of PLA and found that the α 0 form is independent from the α-form.…”
Section: Introductionmentioning
confidence: 99%